Effect of Al concentration on optical parameters of ZnO thin film derived by Sol-Gel dip coating technique - Urper, Osman; Baydogan, Nilgun (Elsevier BV, 2020)
Abstract Pure and Aluminum doped zinc oxide (Al:ZnO) film samples were deposited by the sol–gel dip-coating technique for understand influence of Al concentration on the films crystallization, electrical conductivity and optical transparency. Surface morphology of the film with hexagonal wurtize crystalline structure and high c-axis orientation (in XRD analysis) displayed nanospherical particals (in SEM images). The surface roughness and average grain size increased with Al amount rise in the Al/Zn ratio. The film displayed high transparency (~90%) between 300 and 800 nm for pure and 1, 3 at.% Al concentration levels. The energy band gap, refractive index, and extinction coefficient were affected slightly due to the increasing Al concentration and optical parameters attain gently a maximum value at 3 at.% Al content.